Efficiency of a tailor made NO2 passive sampler and correlations of NO2, PM10 and PM10-bound NO3-in urban air of Chiang Mai (Thailand) - Chanakarn Khamkaew (2018)
This work aims to find out the efficiency of simple equipment in comparison with automatic instruments for NO 2 measurement, to analyze the correlations of air pollutants obtained from different techniques and to investigate the transformation of - gaseous NO 2 to particulate NO 3 on PM 10 particles. PM 10 and NO 2 samples (n = 47) were collected from the air quality monitoring (AQM) station containing automatic equipment in the urban area of Chiang Mai, Thailand, using both a mini volume air sampler and tailor made passive samplers. High correlations of the concentrations obtained from the two different techniques were observed for both PM 10 (r = 0.98) and NO 2 (r = 0.94). The results showed high efficiency of the tailor made passive samplers and a significant possibility of using them for NO 2 measurement. PM 10 and NO 2 concentrations were also well correlated (r = 0.93). A correlation between the particulate phase (PM 10 and PM 10 -bound NO 3- ) was very strong (r = 0.98), while a correlation between NO 2 and - NO 3 (r = 0.90), was also high, which revealed transformation of the gas - to particle -phase on PM 10 particles.